A study of surgical approach to typhoid ileal perforation at a tertiary care hospital of South Gujarat, India - Nema, Archana A.; Darshan, Jitendra R. (International Surgery Journal, 2018)
Background: Even with variety of procedures, typhoid (enteric) perforation still has a high rate of morbidity and mortality. The aim of the present study is to study clinical presentations, to evaluate management pattern of typhoid ileal perforation, to determine mortality and morbidity of perforation and to study the re-exploration rate and causes of re-exploration and its effect on mortality and morbidity Methods: This prospective observational study was conducted in the Departments of Surgery at Surat Municipal Institute of Medical Education and Research, Surat during June 2008 till October 2010. A total 45 patients with typhoid ileal perforation were included in the study. Among them, 32 cases (71%) undergone the simple primary closure of the perforation and peritoneal lavage after refreshing the edge, 7 cases (16%) undergone exploratory laparotomy with proximal loop ileostomy with primary closure and 6 (13%) were operated by exploratory laparotomy with resection anastomosis. Results: Mean duration of the stay for patient undergone PC+PL was 10.20 days and for ileostomy it was 18.4 days and for RA + PL it was 18.6 days. Total 37 incidence of complications were found in 45 cases. Among them wound infection was presented in 16 (43%) and burst abdomen presented in 2 (5%) cases. Fecal fistulae, post-operative collection and pneumonitis were present in 4 (11%) cases each. Conclusion: The overall mortality was found nearly 4 percent in our study. The typhoid ileal perforation should be always treated surgically. There are many operative techniques to deal with, but no one is full proof.